Eksistensi Pesantren Tarekat di Tengah Radikalisme Beragama - Bashori, Achmad Imam; Muhammad Nurush Shobah, Shobah; Ubaidillah, Imam (Mahad Aly Al Fithrah, 2023)
This article discusses about the historical of dynamics of radicalism has accelerated the existence of a stigma about Islamic ideas for the society. Therefore, tarekat boarding school exists to cover Moslem's needs in religious radicalism issues. However, this study aims to establish the existence of tarekat boarding school for facing the radical issues through Islamic values by tarekat boarding school. The method used in this study is descriptive, analytical and historical as material for responding to challenges in the tarekat hierarchy and power in society. Based on the result of the research, the level of awareness of spiritualism as a material for the existence of Islam can be obtained and it can be implicated for the society. Therefore, people's needs who are in the religious radicalism environment can be stopped by spiritualism values. In the other hand, tarekat boarding school are still enthusiastic about building their existence because they refuse to be involved in radicalism.